Penerapan Metode Lightening the Learning Climate untuk Meningkatkan Konsentrasi Belajar Siswa Kelas III pada Pembelajaran Tematik Application of the Lightening the Learning Climate Method to Increase the Learning Concentration of Grade III Students in Th - Faisatul Fitriyah; Mutik Fadhilah (Al-Mudarris: Journal Of Education, 2023)
Lack of student learning concentration during the thematic learning process, which tends to be passive in the learning process. So that students quickly get bored of the teacher's explanation. The purpose of this study was to find out the results of applying the lightening the learning climate method in increasing the learning concentration of class III students at SDN Montok 1. This study used the classroom action research method with the Kemis cycle model which consisted of four stages (planning, implementing, observing, and reflecting). The subjects of this study were class III students at SDN Montok 1. Data collection techniques used observation, interviews, questionnaires, and documentation. The application of the lightening the learning climate method is through a game to train student learning concentration, delivery of material and giving written tests or questions to students to find out student learning outcomes. The results of the percentage of student learning completeness in the application of the lightening the learning climate method at the pre-cycle stage only reached 36%, then increased in Cycle I to 80% and experienced another increase in Cycle II, namely 96%.